Introduction to the Human Body : The Essentials of Anatomy and Physiology. - Tortora, Gerard J.; Derrickson, Bryan (New York : John Wiley, 2007)
Offering a balanced introduction to the human body, this new edition provides a blend of artwork and clear text to ensure that readers gain a solid understanding of the material.
Previous ed.: 2003.
Includes index.
CD-ROM in front pocket.
Text on lining paper.
Keywords: Human anatomy; Human physiology; Body, Human; Health and Wellbeing